Preclinical Pharmacokinetic Considerations for the Development of Antibody Drug Conjugates - Kamath, Amrita V. (Pharm Res, 2014)
Antibody drug conjugates (ADCs) are an emerging new class of targeted therapeutics for cancer that use antibodies to deliver cytotoxic drugs to cancer cells. There are two FDA approved ADCs on the market and over 30 ADCs in the clinical pipeline against a number of different cancer types. The structure of an ADC is very complex with multiple components and considerable efforts are ongoing to determine the attributes necessary for clinical success. Understanding the pharmacokinetics of an ADC and how it impacts efficacy and toxicity is a critical part of optimizing ADC design and delivery i.e., dose and schedule. This review discusses the pharmacokinetic considerations for an ADC and tools and strategies that can be used to evaluate molecules at the preclinical stage.